The results of implementation methods of using cloud technologies as tools of formation high school students' research competencies in profile physics learning - O. V. Merzlykin (Academy of Cognitive and Natural Sciences, 2015)
The purpose of this study is experimental verification of the methods of using cloud technologies as tools of high school students' research competencies forming in profile physics learning. The main task is organization and implementation appropriate pedagogical experiment and processing of it's results. The object of study is high school students' research competencies forming in profile physics learning. The subject of study is using cloud technologies as tools of high school students' research competencies forming in profile physics learning. Main research methods are pedagogical experiment and statistical methods. Profile physics learning is the base of innovation activity both in science and in engineering. That's why forming of high school students' research competencies in profile physics learning will further socio-economic development of society. Realization of the purpose and tasks of profile physics learning is impossible without taking into account the principle of flexibility. This principle implies, in particular, satisfaction of students' individual needs by individual plans and programs in distant learning which is mainly realized by mediated interactions of distant participants of learning process in specialized environment which is functioning on the basis of modern psychological, pedagogical, information and communication technologies (ICT), such as cloud ICT of learning. In our opinion pedagogically reasonable implementation of cloud technologies in profile physics learning promotes the growth of high school students' research competencies.